Karakteristik Sistem Informasi Akuntansi Manajemen Serta Pengaruhnya Terhadap Kinerja Organisasi dengan Desentralisasi Sebagai Variabel Moderating - Meksa Alberian; Bonang Pamungkas Purbananda (CV. Syntax Corporation Indonesia, 2021)
Management Accounting Information System (MAIS) is organization improvement information system. Hospital are one health care system, and specially provide public service to sick communities. This research aims to see the Characteristics of Accounting Information Systems in the form of Broadscope, Aggregation, Integration and Timeliness affect organizational performance by decentralization as a moderation variable. The population of this study is all leaders and staff who work in private hospitals and jayapura city government. The sampling technique which used was purposive sampling, the resulting in 55 samples. The data analysis technique used to tet hypotheses in the study was by using the warpPLS6.0 and SEM Equation analysis.The results showed that broadscope and aggregation had a positive effect on organizational performance, but integration and timeliness had no positive effect on organizational performance. For decentralized variables (moderating), decentralization does not moderate the characteristics of broadscopes, aggregation and timelines. But decentralization moderates negatively to the characteristics of integration